Pengaruh pelatihan pembuatan minuman probiotik serta efikasi diri terhadap minat usaha kelompok masyarakat pendiri bank sampah di kota Depok - Umi Marwati; Laili Savitri Noor; Dian Ratih Laksmitawati; Liliek Nurhidayati (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
This study aimed to determine the effect of counseling and training on the manufacture of probiotic-based health drinks as well as the self-efficacy ability of members of the community group waste management in the city of Depok on the interest in the probiotic beverage business. The 68 respondents included members of the Dahlia Pirus waste bank group (Pondokjaya Village, Cipayung District), Mekar Peduli waste bank (Krukut Sub-district, Limo District) and the Villa Tanah Baru waste bank (Tanah Baru, Beji). This activity involves students. The research method uses multiple regression analysis. The research results show that training has a positive and significant effect on business interest, but self-efficacy has a negative and insignificant effect on business interest.